Intensitas hubungan teman sebaya dengan gaya hidup hedonis siswa - Della Rizki Pratami; Anna Rufaidah; Marta Sundari (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
this study aims to determine the relationship between peer groups and the hedonic lifestyle of students. This research method uses quantitative research with the object of Class XI students. The population in this study was 148 students of Class XI and the number of samples was 108 students. The data analysis technique used is Pearson product moment correlation analysis. The data collection tool used in this study was a questionnaire or questionnaire. The Pearson product moment correlation coefficient generated in this study of 0.216 illustrates that there is a relationship with a low category between peer groups and the hedonic lifestyle of students. The Pearson product moment correlation value is greater than the rtable value of 0.189 so that Ho is rejected and Ha is accepted. The conclusion of this study is that there is a significant unidirectional relationship between peer groups and the hedonic lifestyle of students.